Heavy metals and antibiotic resistance bacteria in marine sediment of Pahang coastal water - Zainal Abidin, Zaima Azira; Chowdhury, Ahmed Jalal Khan (Razi Publishing, 2018)
The presence of heavy metal and antibiotic resistance bacteria in the marine sediment may indicate heavy metal pollution and antibiotic abuse present in the environment. In this study, a total of 89 bacteria isolated from sediment collected in Teluk Chempedak and Pantai Batu Hitam of Pahang coastal water underwent heavy metal resistance test against Chromium, Cadmium, Nickel, Copper and Cobalt. Previously, these isolates were found to exhibit antibiotic resistance capabilities to at least 5 antibiotics tested. Heavy metal resistance pattern for isolates from Teluk Chempedak was in the form of Cr > Ni >Co >Cd = Cu while for isolates from Pantai Batu Hitam showed a pattern of Cr = Ni >Co >Cu >Cd. Further investigation on the identity of selected isolates that exhibited both antibiotic and heavy metals resistance capabilities using 16S rRNA gene sequences revealed isolates with closest similarities to Staphylococcus saprophyticus and Brevundimonas vesicularis..